Modeling cellular systems - Graw, Frederik; Matthäus, Franziska; Pahle, Jürgen (Contributions in mathematical and computational sciences, 2017)
Numerical treatment of the Filament Based Lamellipodium Model (FBLM) -- Understanding the role of mitochondria distribution in calcium dynamics and secretion in bovine chromaffin cells -- IL-2 stimulation of regulatory T cells: a stochastic and algorithmic approach -- Spatio-Temporal Modeling of Membrane Receptors -- Distribution approximations for the chemical master equation: comparison of the method of moments and the system size expansion -- Dynamical features of the MAP kinase cascade -- Sampling from T cell receptor repertoires